Beyond the Information Technology Agreement : Harmonization of Standards and Trade in Electronics - Portugal-Perez, Alberto (2012)
Product standards can have a dual impact on production and trade costs. Standards may impose additional costs on exporters as it may be necessary to adapt products for specific markets (cost-effect). In contrast, standards can reduce exporters' information costs if they convey information on industrial requirements or consumer tastes that would be costly to collect in the absence of standards (informational-effect). Using a new World Bank database of European standards for electronic products, the authors examine the impact of internationally-harmonized European standards on European Union imports. They find that European Union standards for electronic products that are harmonized to international standards have a positive and significant effect on trade. The results suggest that efforts to promote trade in electronic products could be complemented by steps to promote standards harmonization. This might include, for example, re-starting talks to extend the Information Technology Agreement to non-tariff measures and commitments to harmonize national standards in electronic products.